2017
DOI: 10.18632/oncotarget.14470
|View full text |Cite
|
Sign up to set email alerts
|

MiR-24 induces chemotherapy resistance and hypoxic advantage in breast cancer

Abstract: Breast cancer remains one of the leading causes of cancer mortality among women. It has been proved that the onset of cancer depends on a very small pool of tumor cells with a phenotype similar to that of normal adult stem cells. Cancer stem cells (CSC) possess self-renewal and multilineage differentiation potential as well as a robust ability to sustain tumorigenesis. Evidence suggests that CSCs contribute to chemotherapy resistance and to survival under hypoxic conditions. Interestingly, hypoxia in turn regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 71 publications
0
45
0
1
Order By: Relevance
“…miRNAs can either positively or negatively affect the development of tumors depending on their specific downstream target genes by base-pairing with their 3′-UTR. For example, miR-24 can induce chemotherapy resistance and hypoxic advantage in breast cancer through the downregulation of factor inhibiting HIF-1 ( 24 ). miR-497 is significantly correlated with temozolomide-resistance in glioma cells by regulating the insulin-like growth factor 1 receptor/insulin receptor substrate 1 pathway ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can either positively or negatively affect the development of tumors depending on their specific downstream target genes by base-pairing with their 3′-UTR. For example, miR-24 can induce chemotherapy resistance and hypoxic advantage in breast cancer through the downregulation of factor inhibiting HIF-1 ( 24 ). miR-497 is significantly correlated with temozolomide-resistance in glioma cells by regulating the insulin-like growth factor 1 receptor/insulin receptor substrate 1 pathway ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs have been found to be involved in the regulation of the stemness phenotype [4]. For instance, let-7 is one of the main regulators of self-renewal in breast cancer cells [5]; miR-127 and miR-128 have been shown to be important in the modulation of stemness in glioma, since their ablation enhances stem cell renewal and proliferation [6]; and, miR-24 was proven to be a powerful positive regulator of breast CSC features during hypoxic conditions [7]. Moreover, miR-216a-5p-encoded on chromosome 2 on the reverse strand and highly conserved across species-has been shown to act as a tumor suppressor in gastric cancer, breast cancer, hepatocellular carcinoma, small cell lung cancer and renal cancer [8][9][10][11].…”
mentioning
confidence: 99%
“…Investigation of miRNA regulation in the kidney will improve the understanding of renal pathology and may eventually lead to the development of novel treatment strategies for reversing renal fibrosis and dysfunction. Results of previous studies revealed a critical role for miR-152 in human diseases, and miR-152 has been classified as an onco-miRNA in a variety of cancers, including breast, gastric and bladder cancers, and glioma (28)(29)(30). However, to date, a limited number of studies investigated the role of miR-152 in the urinary system.…”
Section: Discussionmentioning
confidence: 99%